Children with Special Needs In the Eyes of Islamic Law and the State - Fitriah, Siti (AKADEMIK: Jurnal Mahasiswa Humanis, 2021)
This study aimed to analyze the legal view Islam and law Positive on the rights of children with disabilities. This research is categorized as field research, and is a type of qualitative research. Then this research also uses an empirical sociological approach, namely non-doctrinal research that is based on primary data. The results of this study show that children with disabilities in South Tangerang City are divided into two categories, namely adults and children. The number for adults is 28 people and for children there are 22 people. People with disabilities are given various trainings that can foster creativity and increase their confidence so they don't feel isolated. In addition, people with disabilities are assisted to open up and undergo the skills process free of charge during the training. The law for the protection of children with disabilities in the Qur'an is contained in two verses, namely: Qs. Abasa 1-10 and Qs. Al-Fath 17. Then the Positive law is contained in Article 5 Paragraph (1) of the Law of the Republic of Indonesia Number 8 of 2016 concerning Persons with Disabilities.